Optic disc and retinal vascular features in first 6 years of Chinese children - Liu, Guina; Jiang, Anna; Cao, Le; Ling, Saiguang; Wang, Xi; Bu, Shaochong; Lu, Fang (Frontiers in Pediatrics, 2023)
Purpose: Retinal microvasculature plays an important role in children’s fundus lesions and even in their later life. However, little was known on the features of normal retina in early life. The purpose of this study was to explore the normal retinal features in the first six years of life and provide information for future research. Methods: Children, aged from birth to six years old and diagnosed with various unilateral ocular diseases were included. Venous phase fundus fluorescein angiography (FFA) images with the optic disc at the center were collected. Based on the ResUNet convolutional neural network, optic disc and retinal vascular features in the posterior retina were computed automatically. Results: 146 normal eyes of 146 children were included. Among different age groups, no changes showed in the optic disc diameter (y=-0.00002x+1.362, R2= 0.025, p=0.058). Retinal vessel density and fractal dimension are linearly and strongly correlated (r=0.979, p<0.001). Older children had smaller value of fractal dimension (y=-0.000026x+1.549, R2=0.075, p=0.001) and narrower vascular caliber if they were less than 3 years old (y=-0.008x+84.861, R2=0.205, p<0.001). No differences were in the density (y=-0.000007x+0.134, R2=0.023, p=0.067) and the curvature of retinal vessels (LnC=-0.00001x-4.657, R2=0.001, p=0.667). Conclusions: Age and gender did not impact the optic disc diameter, vessel density, and vessel curvature significantly in this group of children. Trends of decreased vessel caliber in the first three years of life and decreased vessel complexity with age were observed. The structural characteristics provide information for future research to better understand the developmental origin of the healthy and diseased retina.